TEACHER’S PERCEPTION: TEACHING READING STORYBOARD FOR MENTALLY RETARDED STUDENTS - Lulu Asyrifah; Lies Amin Lestari; Oikurema Purwati (Jurnal Education and Development, 2021)
There is evidence of the benefits of using storyboards. Most of the previous studies focused on the results of applying storyboards for students' achievement, however, there are limited empirical studies on teacher’s perceptions of the application of storyboards in teaching reading for students with special needs, especially mild-mentally retarded students. This study offers a qualitative research that aims to investigate teachers' perceptions of the use of storyboards in teaching reading and its benefits and challenges with two English teachers as the subjects. A semi-structured interview was conducted to collect the data. The findings of this study revealed that there were similarities in teacher’s perception and the benefits derived from the implementation of storyboard, but there were differences in their practice and challenges encountered in the teaching reading process to mild-mentally retarded students.